Primary Pterygium – Comparison of Limbal Conjunctival Autografting Surgery Versus Intra Operative Mitomycin - C (0.02%) After Excision of Primary Pterygium - Singh, Harpal; Thakur, A S; Sharma, B L (National Journal of Community Medicine, 2011)
Pterygium is a fibro vascular encroachment of the conjunctival tissue on the cornea causing variable degree of ocular morbidity. Varies surgical modalities have been developing to reduce the recurrence rate, which is the major limitation of Pterygium surgery. The idea of study is to compare the relative efficacy of two well-known procedure i.e., conjunctival autografting and intra operative Mitomycin-C (0.02%) with recurrence to recurrence and complication.